Tweeting the elections in Belgium. An analysis of social and traditional cross-media patterns - Verdegem, Pieter; D’heer, Evelien; Mechant, Peter (AoIR Selected Papers of Internet Research, 2013)
Mass media have traditionally functioned as an intermediary system between society and political institutions. The rise of social media potentially reconfigures relations between citizens and politicians and challenges traditional media’s position. Via the analysis of Twitter traffic during the 2012 local election in Belgium, this study aims to provide insight in the way different actor types (i.e. politicians, citizens and journalists) and different media outlets (i.e. social and traditional media) are embedded in the Twittersphere. We acknowledge the platform serves as an extension, rather than an alternative for the mainstream media, with high-end Twitter users being mostly established (media) figures. Cross-media linkages often include audiovisual media, both social and traditional media. To conclude, pathways for future research are outlined.